2020
DOI: 10.1039/d0nr01138j
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization of gold nanoclusters with arginine: a trade-off between microtumor uptake and radiotherapy enhancement

Abstract: Gold nanoclusters (AuNC) have strong potential for cancer imaging and therapy. We demonstrate that optimizing the surface chemistry of AuNCs for increased tumor uptake can significantly affect its potential to augment radiotherapy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…[ 25,57,58 ] Moreover, 3D microtumor models are more accurate in predicting in vivo radiotherapy outcomes compared to conventional 2D cultures, as we previously discussed. [ 59 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25,57,58 ] Moreover, 3D microtumor models are more accurate in predicting in vivo radiotherapy outcomes compared to conventional 2D cultures, as we previously discussed. [ 59 ]…”
Section: Resultsmentioning
confidence: 99%
“…[25,57,58] Moreover, 3D microtumor models are more accurate in predicting in vivo radiotherapy outcomes compared to conventional 2D cultures, as we previously discussed. [59] Two glioblastoma spheroid models were established from two radioresistant glioblastoma cell lines: rat F98 [60,61] and human U-87 MG. [62,63] The toxicity of the LaF 3 :Ce nanoscintillators was investigated using dose-escalation studies by assessing the size and viability of the spheroids after 24 h of exposure. In F98 spheroids, the IC 50 of the LaF 3 :Ce nanoscintillators was 2.9 ± 0.1 mg mL −1 (Figure 3A,B), with no notable decrease in viability observed at concentrations below 1.0 mg mL −1 LaF 3 :Ce.…”
Section: Laf 3 :Ce Are Well-tolerated Up To 1 Mg ML −1 In Glioblastommentioning
confidence: 99%
“…Moreover, compared to GSH-protected Au NCs, poly-R conjugated ones exhibited higher quantum yields and prolonged luminescence lifetimes [59]. The potential effectiveness of cationic arginine-stabilized Au NCs (AuSG-2Arg) as diagnostic probes was investigated in cancerous cells lines by Broekgaarden et al The study confirmed that, despite a limited radiotherapeutic potential, AuSG-2Arg were more efficient diagnostic agents, compared to GSH-Au analogs, thanks to their enhanced uptake in glioblastoma models and increased emission intensity at 670 nm [60].…”
Section: Peptidesmentioning
confidence: 99%
“…In the literature, the most frequently reported GBM spheroids comprise only one human or one mouse cell line and are used to test the tumor penetration ability and cytotoxic activity of novel therapies, including cutting-edge nanosystem-based therapies. For instance, in a recent work, Broekgaarden et al used human derived U87MG spheroids and mouse derived F98 spheroids to test the tumor penetration and radiotherapy effectiveness of surfacefunctionalized gold nanoparticles (Broekgaarden et al, 2020). While these models are advantageous when compared with monolayered cell cultures, they still lack relevant TME elements, and do not mimic perivascular regions.…”
Section: Spherical Models-"free" or Matrix-supported Spheroidsmentioning
confidence: 99%